Uncomplicated Urinary Tract Infection: Isolated bacteria, outcome and their susceptibility to antibiotics - Shazia Yasir (ziauddin University, 2024)
Background: Urinary tract infection (UTI) remains a common clinical problem in both the community and health care associated settings. In Pakistan, this is also a common issue and each patient should be carefully assessed to ensure that a correct diagnosis is made and that antimicrobial therapy is appropriately prescribed. UTI is a common problem and it effect's both gender and all ages. Objective: o determine typical symptoms of urinary tract infection locally employing urine test for diagnosis and outcome after use of antibiotics against isolated bacteria. Methods: The cross-sectional descriptive, observational study was conducted at the department of emergency medicine, Ziauddin University Hospital, Karachi from June 2013 to November 2013. Adult patients of either gender with painful and/or frequent maturation were queried for symptoms (history) of urinary tract infection and underwent urine test. Clean catch mid stream urine was collected and the specimens were cultured for isolation of microbial agents of urinary tract infection. The isolated bacteria were identified using biochemical test. The diffusion susceptibility test was used to determine susceptibility of bacterial agents to antibiotics. Data was analyzed by descriptive statistics using SPSS software version 19. Results: In this study, 251 (83.7%) out of 300 patients presented numerous (positive) leucocytes in urine detail report. For these 251 (83.7%) patients, the urine culture and sensitivity was performed. Out of these, E-coli was the most common bacteria found in about 150 (59.8%). The other bacteria are Pseudomonas 18 (7.2%), Proteus 37 (14.7%), Kabsella16 (6.4%), enterococcus 20 (8.0%), and staphylococcus aureus 10 (4.0%). Most of the patients were sensitive to cephalosporin's, amikacnine, and third generation cifixime and ceftrixon. The outcome of patient with appropriate antibiotics was higher at 97.3% for 5 days compared to 83.3% for 3 days. Conclusion: Gram negative bacilli is responsible for urinary tract infection and most frequent isolated bacteria was E-coli. The most effective antibiotics are cepholine, amikacin, and third generation cefixem and ceftrexone in patients. Urinary tract infection occurs within 5 days in our local settings comparing to 3 days in developed communities which can enable emperical use antibiotics with typical symptoms of uncomplicated urinary tract infection for about 5 days in our community. Key Words: Urinary Tract Infection, Isolated Bacteria, Empirical Antibiotics.